TRANSFORMASI KEBIJAKAN PENDIDIKAN MELALUI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Olan Sulistia Rambung; Sion Sion; Bungamawelona Bungamawelona; Yosinta Banne Puang; Silva Salenda (CV. Adiba Aisha Amira, 2023)
Educational transformation is a fundamental change in the approach, methods, and goals of education to address the demands of the modern era. The concept of a